COVID-19 DAN DEMOKRASI DIGITAL DI INDONESIA - Putra, Ferdian Ahya Al; Shidqi, Zia'ulhaq As; Prakoso, Septyanto Galan; Rahma, Adiba Aliyya (Jurnal Studi Komunikasi dan Media, 2024)
During the COVID-19 pandemic, the government made various social restrictions, that affected the democratic process in Indonesia. The prohibition of crowding limited the mobilisation of the public to express their opinions. In response, many people opened up spaces for democratic discussion on digital platforms, utilizing internet of things (IoT). This research will focus on the impact of the COVID-19 pandemic in the digital democracy space. The timeframe from this study would be focused during the COVID-19 pandemic in Indonesia which began from March 2, 2020 as the date of the first announcement of COVID-19 in Indonesia until June 22, 2023 as the date when President Jokowi end the pandemic status. The method used is descriptive qualitative and the cdigital democracy concept for analysis. The data obtain by literature study. The results show that during the COVID-19 pandemic, there are more freedom of expression organized through digital platforms. This study finds COVID-19 pandemic gave significant impact towards societies, especially on the digital democracy context, as new opportunities to express aspirations towards the government. Moreover, the habit of using digital platform for aspiration sharing is still maintained when the status of pandemic ends.